(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the role of the Traditional Games Community (PETRA) administrators in preserving local wisdom through bamboo stilt games for children in Tanjung Rejo Village. Preserving traditional games is important because children’s interest in local culture-based games is decreasing due to technological developments and the dominance of digital games. The study used a qualitative approach with a case study type. The research subjects consisted of two PETRA Community administrators and one community member who participated in the bamboo stilt game activities. Data were collected through interviews, observations, and documentation, then analyzed descriptively. The results showed that the PETRA Community administrators acted as guides, educators, and friends in implementing bamboo stilt games. As guides, the administrators provided direction, assistance, assistance, and motivation to the children. As educators, the administrators introduced bamboo stilts as a cultural heritage while instilling local wisdom values, such as discipline, cooperation, responsibility, courage, sportsmanship, and mutual respect. As friends, the administrators built close relationships so that children felt comfortable participating in the activities. The research findings confirm that community-based communities contribute to the preservation of local wisdom through the inheritance of traditional games that not only maintain cultural heritage but also strengthen children’s character formation.